Die Neuropsychologie und der Sprach- bzw. Fremdsprä- chengebrauch - ZAWADZKA, Elżbieta (Wydawcnictwo Naukowe UAM, 1988)
The aim of this paper is to present some results of the neuropsychological researches and their consequences for the glottodidactical theory. The author describes the main conceptions related to the organization and functioning of the brain during the processing of the verbal stimuli and also the results of the researches on the specialization of the left and right hemispheres. There has been discussed the problem of lateralization and its different conceptions, also with reference to bilingual persons. In the paper the attention has been paid to the consequences for the glottodicactic resulting from the neuropsychological researches, especially those resulting from the so-called critical period hypothesis about foreign language acquisition.